Implementation of a Web-Based Raw Material Inventory Information System Using the Prototype Method: A Case Study at PT. XYD - Susanto, Dede Agus; Firmansyah, Andri; Nawangsih, Ismasari (International Journal Software Engineering and Computer Science (IJSECS), 2024)
PT. XYD is a manufacturing company in the automotive industry and serves as a key vendor for the Wuling car brand, producing parts for models such as Confero, Cortez, Almaz, Air Ev, and Alvez. As production volume and the complexity of managing raw materials have increased, PT. XYD faces challenges in maintaining the accuracy of inventory data, particularly in the warehouse. Errors in data entry can disrupt the production process, leading to delays in product delivery to customers. To address this issue, this study developed and implemented a web-based raw material inventory information system using the prototype method. This method was chosen for its ability to accelerate the development process through iterative improvements based on user feedback. The system was designed using Unified Modeling Language (UML) to illustrate the system’s model and structure. The implementation of this system aims to enhance efficiency and accuracy in managing inventory data, ultimately minimizing the risk of errors, increasing productivity, and ensuring smooth company operations. The results of the study demonstrate that the system successfully facilitates the digitalization of ordering and inventory reporting processes, reducing reliance on manual processes and improving the speed and accuracy of data processing at PT. XYD.